The Impact of GeoGebra-Assisted Instruction on Students' Performance in Geometric Construction: Exploring Teacher Beliefs and Classroom Practices - Yelewere, Festus; Bonyah, Ebenezer; Adu Obeng, Benjamin (International Journal of Mathematics and Mathematics Education, 2026)
Purpose – This study examined the effect of GeoGebra on students’ performance in geometric construction, with emphasis on students’ perceptions and teachers’ beliefs and instructional practices in a Ghanaian senior high school context. Methodology – Guided by Social Constructivist Theory, the Technology Acceptance Model, and Cognitive Load Theory, the study adopted a pragmatic paradigm using a convergent mixed-methods design. The research was conducted at Nkyeraa Senior High School in the Wenchi Municipality of Ghana. The sample comprised 71 Form 3 students selected into experimental and control groups and five mathematics teachers. Quantitative data were collected using pre-test and post-test achievement tests and a ten-item five-point Likert scale questionnaire on students’ perceptions. Independent samples t-tests were used for data analysis. Qualitative data were gathered through semi-structured interviews with teachers and analyzed using thematic analysis. Findings – Pre-test results showed no significant difference between the experimental and control groups, indicating equivalence. Post-test results revealed that students taught using GeoGebra performed significantly better than those taught through traditional methods. Students demonstrated positive perceptions of GeoGebra-assisted learning, with a grand mean score of 4.37. Four themes emerged from teacher interviews: beliefs about GeoGebra, perceived impact on learning, instructional strategies, and challenges and support needs. Novelty – The study integrates students’ achievement, perceptions, and teachers’ beliefs within a single mixed-method framework in a Ghanaian senior high school setting. Significance – The findings benefit mathematics teachers, curriculum developers, and policymakers by supporting the integration of GeoGebra, teacher professional development, and improved ICT infrastructure in mathematics education.